Removal of sodium compounds from Co/SBA-15 catalysts for Fischer-Tropsch Synthesis - Silva, Lidiane Sabino da; Cher, Gabriela Gonzaga; Baldanza, Maria Auxiliadora Scaramelo; Silva, Victor Luis dos Santos Teixeira da; Arroyo, Pedro Augusto (Acta Scientiarum. Technology, 2020)
In the present work, the synthesis of Co/SBA-15 catalysts intended for Fischer-Tropsch (FT) synthesis was performed. During the synthesis of catalysts there was contamination of samples with sodium nitrate due to the nature of the reducing agent used for the synthesis of metallic phase. This kind of impurity is not advantageous for the FT reaction. Attempts at removal of sodium compounds were carried out by means of simple leaching treatments, using ethanol and acid ethylenediaminetetraacetic (EDTA) as solvent and complexing agent, respectively, followed by heat treatment at temperatures of 150 or 300Â°C. It was possible to conclude that the treatment using EDTA was more effective in removing almost all the alkaline phase of samples, despite the occurrence of oxidation, agglomeration, and removal of the metal nanoparticles in this process. In addition, there were no significant differences in the product selectivity of FT synthesis of the catalysts after sodium removal, although the nanoparticles were larger than 10 nm.